N-doped carbon quantum dots/TiO2 composite with improved photocatalytic activity - Martins, Natercia C. T.
A new composite of TiO2 (P25) and N-doped carbon quantum dots (P25/NCQD) was prepared by a hydrothermal method and was used for the first time as catalyst of the photo-oxidation of NO under UV and visible light irradiation. P25/NCQD composite exhibited a NO conversion (27.0%) more than two times higher of that observed for P25 (10%) under visible light and the selectivity of the process was increased from 37.4% to 49.3%. The composite also showed better photocatalytic performance than P25 in the UV region with increases of 36.3% on NO conversion and 16.8% on selectivity. Moreover, compared with P25, the photodegradation ratio of methylene blue was enhanced from 68% to 91% after UV irradiation for 1 h. NCQD played a crucial role on the photocatalytic activity improvement of P25/NCQD, increasing visible light absorption, slowing the recombination and improving the charge transfer. (C) 2016 The Authors. Published by Elsevier B.V.